COLOR SENSATION - A PSYCHOLOGICAL ANALYSIS: रंग संवेदना - एक मनोवैज्ञानिक विश्लेषण - Burman, Mamta (International Journal of Research -GRANTHAALAYAH, 2014)
Experimental studies in psychology began before experimental studies of sensation began. Tichner, Boring, Jastrow, Elesh Young, Helmholz, Herring, Ladd, Fankerlin, etc. carried out experimental studies of sensation. The experimental study of different sensations in various disciplines of science was started in the early nineteenth century. Wunt 1874 distinguished differences between sentencing and articulation. In the nineteenth century, more than fifty percent of work in the field of psychology was related to sensory psychology. Sensation is a normal, simple and first process of the brain. Light is a radiated energy, the waves produced from it are studied as a magnetic or electric current. Sunlight consists of waves of different colors. Newton 1966, with the help of prism, observed that sunlight has all the colors of rainbow and sunlight is made up of different colors. If the sensation arising from various stimuli touches the collector (the brainstem of the brain), a vibrations are produced in the body’s nerve which is called electrochemical power. This nervous flow plays its role in sending sensory messages to the respective center in the brain through the sensory nerve. To a certain extent, stimulants are capable of producing sensations in humans. The electromagnetic waves produced by excitation, ranging in length from 400 micro millimeters to 800 micromillimeters, are capable of producing visual sensations. मनोविज्ञान में प्रयोगशालीय अन्वेषण से पहले ही संवेदना का प्रयोगात्मक अध्ययन प्रारम्भ हुआ । टिचनर, बोरिंग, जैस्ट्रो, एलेश यंग, हेल्महोल्ज, हेरिंग, लैड, फैंक्रलिन आदि ने संवेदना का प्रायोगात्मक अध्ययन किया । विभिन्न संवेदनाओं का प्रयोगात्मक अध्ययन विज्ञान के विभिन्न विषयों में उन्नीसवीं शताब्दी के प्रारम्भ में ही आरम्भ हो गया था। वुण्ट 1874 ने संवदेना और प्रत्यक्षीकरण में अंतर स्पष्ट किया। उन्नीसवीं शताब्दी में मनोविज्ञान के क्षेत्र में पचास प्रतिशत से अधिक कार्य संवेदना मनोविज्ञान से संबंधित था। संवेदना मस्तिष्क की सामान्य, सरल तथा प्रथम प्रक्रिया है। प्रकाश एक विकीर्ण ऊर्जा है, इससे उत्पन्न तरंगों का अध्ययन चुम्बकीय अथवा विद्युतीय धारा के रूप में किया जाता हैं। सूर्य के प्रकाश में विभिन्न रंगों की तरंगें सम्मिलित होती है। न्यूटन 1966 ने प्रिज्म की सहायता से देखा कि सूर्य के प्रकाश में इन्द्रधनुष के संभी रंग होते है एवं सूर्य का प्रकाश विभिन्न रंगों से मिलकर बना हैं। विभिन्न उद्दीपक से उत्पन्न संवेदना संग्राहको (ज्ञानवाही स्नायुतंत्र) को स्पर्श करती है तो शरीर के स्नायु में एक स्पन्दन उत्पन्न होता है जिसे विद्युत रासायनिक शक्ति कहा जाता है। यही स्नायु प्रवाह ज्ञानवाही स्नायु के द्वारा मस्तिष्क में सम्बन्धित केन्द्र तक संवेदना रूपी संदेश पहुँचाने में अपनी भूमिका निभाता है। एक निश्चित सीमा तक उत्तेजक मनुष्य में संवेदना उत्पन्न करने में सक्षम होते है। उत्तेजना से उत्पन्न विद्युत चुम्बक तरंगे जिनकी लंबाई 400 माइक्रो मिलीमीटर से 800 माइक्रोमिलीमीटर तक होती है, दृष्टि संवेदनाएँ उत्पन्न करने में सक्षम होती हैं।